Manajemen Peserta Didik dalam Mengaktualisasikan Nilai-Nilai Karakter di Satuan Pendidikan - Ilyasin, Mukhamad (FENOMENA, 2019)
One of components in school-based management that must be met is the student management. Management is intended to be related to the values of character education. It is arranged in a structured way from planning, implementation and control. The management consists of inculcation of values in the curriculum of learning activities, an assessment system for the behavior of educators and education personnel or other related components. Actualization of character values in the management of students is translated into several components of student management, namely: needs analysis, recruitment, selection, orientation, and class division that is included in the pre-school stages. Whereas at the school stage consists of student development components and recording and reporting and at the post-school stage relating to graduation.